Creative thinking in elementary education: Reliable assessment instruments for science and social studies - Fitri Alfarisa; Andika Arisetyawan; Farid Rizqi Maulana; Nadhila Yanama Lathifah; Sinta Afriani; Mashudi Mashudi (Jurnal Penelitian dan Evaluasi Pendidikan)
Creative Thinking Skills (CTS) are essential abilities that students must possess. CTS can be stimulated by teachers through the learning and assessment processes. The scarcity of specific CTS instruments, particularly in the subject of science and social studies, presents a gap that this research aims to address. The objectives of this study are to 1) develop a test instrument for measuring CTS in Science and Social Studies to enhance students' 21st-century competencies, 2) evaluate the quality of the developed CTS instrument, and 3) examine the CTS profile of fifth-grade elementary school students in Serang City. This research employs a development methodology based on Mardapi's instrument development model, which consists of nine steps, starting from constructing test specifications to interpreting test results. The developed instrument takes the form of an essay-based CTS test for fifth grade, consisting of 10 items. The CTS indicators include fluency, flexibility, originality, and elaboration. Content validity was established through expert judgment, with agreement levels assessed using Aiken's V index. Construct validity was tested using Confirmatory Factor Analysis, and reliability was measured with Cronbach's Alpha. Data analysis utilized the R program to assess the characteristics of the developed CTS instrument.